Workplace learning in context - Rainbird, Helen; Fuller, Alison; Munro, Anne, 1956- (Routledge, 2004)
Combines a critical analysis of the organizational and employment context of workplace learning with an understanding of theories of learning. It brings new ideas and an understanding of the social context of the workplace.